Global weak solutions for a two-component Camassa–Holm system with an arbitrary smooth function. Issue 12 (10th September 2018) - Zheng, Rudong; Yin, Zhaoyang
Abstract: In the paper, by the approximation of smooth solutions and a regularization technique, we show the existence and uniqueness of global weak solutions for a two-component Camassa–Holm system with an arbitrary smooth function provided the initial data satisfy some certain sign condition.